Building community at distance: a datathon during COVID-19. Issue 4 (4th August 2020) - Fritz, Samantha; Milligan, Ian; Ruest, Nick; Lin, Jimmy
Abstract : Purpose: This paper aims to use the experience of an in-person event that was forced to go virtual in the wake of COVID-19 as an entryway into a discussion on the broader implications around transitioning events online. It gives both practical recommendation to event organizers as well as broader reflections on the role of digital libraries during the COVID-19 pandemic and beyond. Design/methodology/approach: The authors draw on their personal experiences with the datathon, as well as a comprehensive review of literature. The authors provide a candid assessment of what approaches worked and which ones did not. Findings: A series of best practices are provided, including factors for assessing whether an event can be run online; the mixture of synchronous versus asynchronous content; and important technical questions around delivery. Focusing on a detailed case study of the shift of the physical team-building exercise, the authors note how cloud-based platforms were able to successfully assemble teams and jumpstart online collaboration. The existing decision to use cloud-based infrastructure facilitated the event's transition as well. The authors use these examples to provide some broader insights on meaningful content delivery during the COVID-19 pandemic. Originality/value: Moving an event online during a novel pandemic is part of a broader shift within the digital libraries' community. This paper thus provides a useful professional resource for others exploring this shift, as well as those exploring new program delivery in the post-pandemic period (both due to an emphasis on climate reduction as well as reduced travel budgets in a potential period of financial austerity).